2018
DOI: 10.1002/hbm.24194
|View full text |Cite
|
Sign up to set email alerts
|

Detailed view on slow sinusoidal, hemodynamic oscillations on the human brain cortex by Fourier transforming oxy/deoxy hyperspectral images

Abstract: Slow sinusoidal, hemodynamic oscillations (SSHOs) around 0.1 Hz are frequently seen in mammalian and human brains. In four patients undergoing epilepsy surgery, subtle but robust fluctuations in oxy‐ and deoxyhemoglobin were detected using hyperspectral imaging of the cortex. These SSHOs were stationary during the entire 4 to 10 min acquisition time. By Fourier filtering the oxy‐ and deoxyhemoglobin time signals with a small bandwidth, SSHOs became visible within localized regions of the brain, with distinctiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…However, existing data allow a reasonable estimate. For example: (i) rat arterial strips elicited vasomotion with a velocity of 100 μm/s (Seppey et al, 2009), while (ii) hemodynamic oscillations propagating on the surface of the human brain (probably related to vasomotion) had an average velocity of 800 μm/s (Noordmans et al, 2018). Even when the higher end of velocities is considered, the resulting wavelength of cerebral vasomotion (e.g., 8 mm) is still two orders of magnitude smaller than that of the human arterial pulse wave (e.g., 1 m, calculated based on a velocity of 1 m/s and a frequency of 1 Hz, Stefanovska, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…However, existing data allow a reasonable estimate. For example: (i) rat arterial strips elicited vasomotion with a velocity of 100 μm/s (Seppey et al, 2009), while (ii) hemodynamic oscillations propagating on the surface of the human brain (probably related to vasomotion) had an average velocity of 800 μm/s (Noordmans et al, 2018). Even when the higher end of velocities is considered, the resulting wavelength of cerebral vasomotion (e.g., 8 mm) is still two orders of magnitude smaller than that of the human arterial pulse wave (e.g., 1 m, calculated based on a velocity of 1 m/s and a frequency of 1 Hz, Stefanovska, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The DMN is a network of brain regions that show highly correlated activity during rest and reduced activation during attention-demanding tasks (Raichle et al, 2001), and contains the medial prefrontal and posterior cingulate cortices (both known to be involved in central autonomic regulation) as core regions (Bär et al, 2015). The DMN is characterized by blood-oxygen-level-dependent (BOLD) fMRI signal fluctuations around 0.1 Hz (Mantini et al, 2007; Jerath et al, 2012; Rayshubskiy et al, 2014; Noordmans et al, 2018). Although the DMN average frequency of 0.1 Hz synchronizes activity in widespread regions of the brain and is highly correlated with respiration (Birn et al, 2008; Jerath et al, 2012), the precise impact of respiratory fluctuations on the DMN is poorly understood (Jerath and Crawford, 2015) and large amplitude 0.1 Hz hemodynamic oscillations observed in human fMRIs indicative of cortical resting states are rarely considered (Rayshubskiy et al, 2014).…”
Section: Linking Slow Breathing To Global Changes In Brain Activitymentioning
confidence: 99%
“…It has been hypothesized that, via neural activity oscillations around 0.1 Hz possibly attributed to SARs (Jerath et al, 2012), respiratory impulses during slow breathing may synchronize with the DMN (Zaccaro et al, 2018). Since slow, local propagating hemodynamic waves appear related to vasomotion and perfusion of active functional areas (Aalkjaer et al, 2011), respiratory-linked neuronal oscillations around 0.1 Hz could couple the demands of neural activity to perfusion and improve brain tissue capacity (Noordmans et al, 2018), enhancing physiological function. Studies investigating the link between respiration and brain activity have suggested that respiratory rhythms may be an organizing principle of cortical oscillations in the human brain (Herrero et al, 2018).…”
Section: Linking Slow Breathing To Global Changes In Brain Activitymentioning
confidence: 99%
“…Examples of HSI usability within (bio)medical disciplines range from perioperative support with guidance of the surgeon to delineate the right resection margins of lentigo maligna or cerebral neoplasms to assessing diabetic foot ulcer development risk. 2 6 Other proof-of-concepts measured the oxygen saturation (OS) of various organs 7 ; assessed the presence of molecules such as cholesterol, melanin, and hemoglobin 8 , 9 ; enhanced the surgeon's vision in oncologic surgery and laparoscopy 10 13 ; predicted hemorrhagic shock and appraising hemodynamics 14 16 ; classified corneal injury 17 ; augmented contrast for histologic examinations 18 , 19 ; and detected neoplasms of the skin, mouth, colon, brain, and others. 3 , 5 , 20 22 In ophthalmology, HSI can be used to assess the state and distribution of chromophores, such as cytochrome C, and assess the metabolic status of hemoglobin in the context of retinal blood vessel oxygenation.…”
Section: Introductionmentioning
confidence: 99%